2014
DOI: 10.1111/anu.12202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the diet on seahorse (Hippocampus hippocampus) growth, body colour and biochemical composition

Abstract: The short-snouted seahorse (Hippocampus hippocampus) is a benthic fish that bases its survival on camouflage with the environment; therefore, both in wild and in captivity specimens, differences in coloration have been observed. This study was conducted to study the effect of five different diets, based on Artemia and frozen mysis, on fish survival, growth, skin colour parameters and biochemical composition. After 102 days of feeding different diets, no effect was observed on fish survival, growth, protein, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…After 102 days, no significant differences ( P ≥ 0.05) in length or weight between the diets were found as observed by Segade et al . (). The biochemical composition of the diets used is shown in Tables & .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…After 102 days, no significant differences ( P ≥ 0.05) in length or weight between the diets were found as observed by Segade et al . (). The biochemical composition of the diets used is shown in Tables & .…”
Section: Resultsmentioning
confidence: 97%
“…The feeding ratio was maintained around 150 g kg −1 of the overall biomass throughout the whole trial following the recommendations by other authors (Woods & Valentino ; Woods ; Palma et al . ; Segade et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Moreover, recently Segade et al . () showed the effect of diet on seahorse ( Hippocampus hippocampus ) body colour using MVS.…”
Section: Preharvestmentioning
confidence: 99%
“…Researchers have used different optical sensors for measuring and determining skin colour in fish. Pavlidis et al (2006) Segade et al (2014) showed the effect of diet on seahorse (Hippocampus hippocampus) body colour using MVS.…”
Section: Individual Fish Features Analysismentioning
confidence: 99%
“…However, the natural source of seahorse has dramatically reduced owing to overfishing, unsustainable trade, and habitat destruction (Qian et al 2012). Therefore, seahorses became the first commercially valuable marine genus to be protected and included in Appendix II of the Convention on International Trade in Endangered Species (CITES) in 2004 (Segade et al 2015).…”
Section: Introductionmentioning
confidence: 99%